2013
DOI: 10.3390/ma6114911
|View full text |Cite
|
Sign up to set email alerts
|

Bone Tissue Engineering with Adipose-Derived Stem Cells in Bioactive Composites of Laser-Sintered Porous Polycaprolactone Scaffolds and Platelet-Rich Plasma

Abstract: Three-dimensional porous polycaprolactone (PCL) scaffolds with consistent inter-pore channels, 83% porosity and 300–400 μm pore size were fabricated via selective laser sintering. The PCL scaffold was combined with platelet-rich plasma (PRP) to form a bioactive composite and studied for potential application in bone tissue engineering using porcine adipose-derived stem cells (PASCs). The PCL/PRP/PASCs construct showed enhanced cell seeding efficiency and synergistically increased the differentiation capability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…Abundant examples in the literature have addressed the positive effects of PRP on bone regeneration by combining with different biomaterials and various cell sources [ 40 ]. Improvement of osteogenesis of ASCs by PRP was also confirmed in a previous study by us [ 41 ]. Therefore, we hypothesize the incorporation of PRP and BCP as the osteo-inductive and osteo-conductive factor in the thermo-gelling hydrogel HA-CPN would influence the osteogenesis of ASCs.…”
Section: Introductionsupporting
confidence: 84%
“…Abundant examples in the literature have addressed the positive effects of PRP on bone regeneration by combining with different biomaterials and various cell sources [ 40 ]. Improvement of osteogenesis of ASCs by PRP was also confirmed in a previous study by us [ 41 ]. Therefore, we hypothesize the incorporation of PRP and BCP as the osteo-inductive and osteo-conductive factor in the thermo-gelling hydrogel HA-CPN would influence the osteogenesis of ASCs.…”
Section: Introductionsupporting
confidence: 84%
“…Bone tissue engineering has been widely studied and typically involves combining scaffolds with various growth factors and cell sources ( 22 ). Searching for an optimal scaffold for bone regeneration remains an unsolved and interesting challenge for researchers.…”
Section: Discussionmentioning
confidence: 99%
“…Adipose-derived stem cells (ADSCs), which are recognized as a type of mesenchymal stem cell ( 18 ), have a similar morphology, differentiation capacity, and phenotype to bone marrow stromal cells (BMSCs) ( 19 ). Zuk et al ( 20 , 21 ) initially reported the existence of a mesenchymal stromal/stem cell isolated from adipose tissue, and since then the osteogenic potential of ADSCs in vitro and in vivo has been demonstrated in numerous studies ( 19 , 22 , 23 ). As compared with BMSCs, ADSCs are easier to obtain and can be harvested in large numbers from small volumes of adipose tissue.…”
Section: Introductionmentioning
confidence: 99%
“…The device was coated on all the sides by the ADMSCs in the medium. After being incubated at 37°C for 1 hour to allow cell attachment, DMEM with 10% FBS (Gibco, USA) was added for 24 h. The seeded device was maintained for 3, 7, and 14 days, independently [ 13 ]. The ADMSC seeded device was washed with PBS, fixed in 1% glutaraldehyde in Sorensen phosphate buffer for 24 hours and dehydrated in a graded ethanol series and the morphology of adhered and attached ADMSC on the device was visualized by Scanning Electron Microscopy (Hitachi 2500).…”
Section: Methodsmentioning
confidence: 99%